2008
DOI: 10.1371/journal.pntd.0000212
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Neuropathy in Leprosy—Comparing Diagnostic Tests in a Large Prospective Study (the INFIR Cohort Study)

Abstract: BackgroundLeprosy is the most frequent treatable neuromuscular disease. Yet, every year, thousands of patients develop permanent peripheral nerve damage as a result of leprosy. Since early detection and treatment of neuropathy in leprosy has strong preventive potential, we conducted a cohort study to determine which test detects this neuropathy earliest.Methods and FindingsOne hundred and eighty-eight multibacillary (MB) leprosy patients were selected from a cohort of 303 and followed for 2 years after diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
1
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 31 publications
(34 reference statements)
5
72
1
15
Order By: Relevance
“…In this first prospective study investigating ultrasonographic nerve abnormalities in leprosy we found that the neural involvement may not improve after treatment, in accordance with the findings of previous clinical and electrophysiological studies [1719,2427]. Furthermore, US findings can worsen despite the operational classification and the presence of reactions, as demonstrated by the CSA increase in the CF nerve in PB and in patients without reactions and by the increased frequency of echogenicity abnormalities detected in the post-treatment evaluation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this first prospective study investigating ultrasonographic nerve abnormalities in leprosy we found that the neural involvement may not improve after treatment, in accordance with the findings of previous clinical and electrophysiological studies [1719,2427]. Furthermore, US findings can worsen despite the operational classification and the presence of reactions, as demonstrated by the CSA increase in the CF nerve in PB and in patients without reactions and by the increased frequency of echogenicity abnormalities detected in the post-treatment evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that MDT does not stop the progression of nerve function impairment [5,17,26,27]. The present study shows that, similar to the results concerning nerve function, the anatomic nerve changes caused by leprosy may not improve significantly with treatment.…”
Section: Discussionsupporting
confidence: 71%
“…Early identifi cation combined with the proper treatment of leprosy reactions can be an effective strategy to prevent physical impairment in leprosy 13,14 . Prednisone is the drug of choice not only for the treatment of leprosy reactions and silent neuritis events 21 but also to reduce swelling and prevent further physical impairment 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiologische Untersuchungen konnten bei 20-50 % der Lepra-Patienten eine subklinische Neuropathie nachweisen. Dabei fielen die Untersuchungen der Nervenleitung der sensiblen Fasern und der Wärmewahrnehmungsschwelle am frühes-ten pathologisch aus (früher als bei der Kälte-wahrnehmung) [11].…”
Section: Ridley-joping-klassifikation | Diese Beschreibt Inunclassified